2014
DOI: 10.1089/ten.tea.2014.0026
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mechanical Stimulation on Mineralization in Differentiating Osteoblasts in Collagen-I Scaffolds

Abstract: Developing a viable and functional bone scaffold in vitro that is capable of surviving and bearing mechanical load in vivo requires an understanding of the cell biology of osteoprogenitor cells, particularly how they are influenced by mechanical stimulation during cell differentiation and maturation. In this study, mechanical load was applied using a modified FlexCell plate to impart confined compression to collagen-I scaffolds seeded with undifferentiated murine embryonic stem cells. The activity, presence, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…In a previous study performed by our group, FRAP showed that there was a significant difference between average maximum percent recovery in early (Day 5) and late-differentiated (Days 15-30) gels in the presence and absence of loading (Figure 2A, a previously published result) (16). In this study, gels treated with octanol and AGA showed a significant reduction in fluorescence recovery values ( Figure 2B).…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…In a previous study performed by our group, FRAP showed that there was a significant difference between average maximum percent recovery in early (Day 5) and late-differentiated (Days 15-30) gels in the presence and absence of loading (Figure 2A, a previously published result) (16). In this study, gels treated with octanol and AGA showed a significant reduction in fluorescence recovery values ( Figure 2B).…”
Section: Resultssupporting
confidence: 80%
“…Specifically, confined compression of early-differentiated cells produced a honeycomb structure to the mineralization present, a quality associated with late osteoblast/early osteocyte activity (16). Prestimulated cells also upregulated early and late osteoblast markers (16). In this current study, gap This article has been peer-reviewed and accepted for publication, but has yet to undergo copyediting and proof correction.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The effects of mechanical stimuli on osteoblastic cells have been studied in 2-D culture by applying cyclic tensile strain or compression [Ziros et al, 2002;Visconti et al, 2004;Koike et al, 2005]. Furthermore, some studies observed the effects of biomechanical forces on osteoblastic cells in 3-D culture systems [Duty et al, 2007;Sanuki et al, 2007;Rath et al, 2008;Dumas et al, 2009;Chatterjee et al, 2010;Damaraju et al, 2014Damaraju et al, , 2015Tanaka and Tachibana, 2015]. Other studies observed cell growth in 3-D cultures in the absence of any mechanical stimuli [Cao et al, 2003].…”
mentioning
confidence: 99%